2011
DOI: 10.1007/s11906-011-0224-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune Mechanisms in Hypertension

Abstract: Inflammation plays an important role in the pathogenesis of hypertension. Innate and adaptive immune response may contribute to this process. The mechanisms implicating immune response in hypertension are still elusive. To date, the evidence originates in three major areas of data: cytokine production, central nervous system (CNS) stimulation, and kidney damage. The cytokine microenvironment can become proinflammatory and propagate low-grade inflammation, which may contribute to vascular injury and end-organ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 39 publications
0
49
0
Order By: Relevance
“…[9][10][11] Harrison et al 9 have suggested a working hypothesis for the mechanism behind this phenomenon. They assert that hypertensive stimuli, such as angiotensin II and high salt, cause a modest elevation in blood pressure, resulting in the development of prehypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Harrison et al 9 have suggested a working hypothesis for the mechanism behind this phenomenon. They assert that hypertensive stimuli, such as angiotensin II and high salt, cause a modest elevation in blood pressure, resulting in the development of prehypertension.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The metabolic syndrome is a risk factor for atherosclerosis, 37 and it is well established that inflammation has a pivotal role in atherosclerosis. 38 Inflammation is also relevant in the high-fructose diet model.…”
Section: Discussionmentioning
confidence: 99%
“…20 Our study demonstrates that a high-fructose diet can enhance vascular inflammation, which plays a role in vascular injury and ultimately in hypertension. 5 Using Wistar rats fed 10% fructose in drinking water for 38 weeks, Tan et al 40 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations